Parental control and depressive symptoms in college freshmen with myopia: the mediating role of vision-related quality of life - Liang, Gang; Dong, Xing-Xuan; Li, Dan-Lin; Liu, Min-Xin; Yin, Zhi-Jian; Li, Yue-Zu; Zhang, Tianyang; Pan, Chen-Wei (Frontiers in Psychiatry, 2025)
ObjectivesMyopia is considered to be associated with depressive symptoms. Perceived parental control plays a critical role in children and adolescents’ mental health. The present study aimed to examine the role of myopia in depressive symptoms and whether parental control contributes to depressive symptoms via vision-related quality of life (QoL) in myopic students.MethodsThis study investigated the mediating role of vision-related QoL between parental control and depressive symptoms among Chinese children and adolescents with myopia. A total of 2014 college freshmen in China were included. Correlation analysis and mediation analysis were conducted. Mediation models were used to assess the potential mechanism of vision-related QoL in the association between parental control and depressive symptoms.ResultsIn our sample, participants with myopia were less likely to develop depressive symptoms than those without myopia (P = 0.01). Subsequently, analysis within the myopic group revealed that vision-related QoL significantly mediated the relationship between parental control and depressive symptoms, accounting for 15.69% (maternal control) and 18.86% (paternal control) of the total effect.ConclusionsThis study highlights the important role of myopia for depressive symptoms in college freshmen and demonstrates that vision-related QoL significant mediates the relationship between parental control and depressive symptoms.